THE STRUGGLE OF JUDY HOPPS IN THE MOVIE ZOOTOPIA - Esti Yenika; Ferry Kurniawan (Politeknik Negeri Sriwijaya, 2020)
Abstract: The aims of this research are to find out the characterizations of Judy Hopps in the movie Zootopiaand the struggles of Judy Hopps to make her dream come true. The method used was descriptive method. Incollecting the data, the researcher downloaded and watched the movie, found the script movie to get fullunderstanding about the content in the movie, found out the struggle in Judy Hopps character and noted theutterances in Judy Hopps character as the data for analysis based on Feminism theory by Karl Max. There arefive characterizations found in Judy Hopps’ character, they are; clever, energetic, heroic, kind-hearted and nevergive up. The findings revealed Judy Hoops has a dream to make the world better place. In achieving her dream,she faced stereotypes, prejudice, discrimination, violence, and segregation. She struggled for being a femalepolice officer, for raising social class and for gender equality.